Multiple resistance factors collectively promote inoculum-dependent dynamic survival during antimicrobial peptide exposure in Enterobacter cloacae. - Andrew N Murtha; Misha I Kazi; Eileen Y Kim; Facundo V Torres; Kelly M Rosch; Tobias Dörr (PLoS Pathogens)
Antimicrobial peptides (AMPs) are a promising tool with which to fight rising antibiotic resistance. However, pathogenic bacteria are equipped with several AMP defense mechanisms, whose contributions to AMP resistance are often poorly defined. Here, we evaluate the genetic determinants of resistance to an insect AMP, cecropin B, in the opportunistic pathogen Enterobacter cloacae. Single-cell analysis of E. cloacae's response to cecropin revealed marked heterogeneity in cell survival, phenotypically reminiscent of heteroresistance (the ability of a subpopulation to grow in the presence of supra-MIC concentration of antimicrobial). The magnitude of this response was highly dependent on initial E. cloacae inoculum. We identified 3 genetic factors which collectively contribute to E. cloacae resistance in response to the AMP cecropin: The PhoPQ-two-component system, OmpT-mediated proteolytic cleavage of cecropin, and Rcs-mediated membrane stress response. Altogether, our data suggest that multiple, independent mechanisms contribute to AMP resistance in E. cloacae.